2010
DOI: 10.1111/j.1463-1326.2009.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture: is it effective for treatment of insulin resistance?

Abstract: Insulin resistance (IR) is closely associated with obesity, type 2 diabetes mellitus (T2DM), hypertension, polycystic ovary syndrome (PCOS), non-alcohol fatty liver diseases (NAFLD) and metabolic syndrome and is also a risk factor for serious diseases such as cardiovascular diseases. Pharmacological treatments available for IR are limited by drug adverse effects. Because acupuncture has been practiced for thousands of years in China, it has been increasingly used worldwide for IR-related diseases. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 119 publications
4
84
0
2
Order By: Relevance
“…In this respect, although the distribution of our data is non-parametric, we can state that preacupuncture levels of insulin were in the higher centiles and postacupuncture values decreased to the lower centiles. This suggests normalisation of insulin values and improved insulin sensitivity with acupuncture treatment, [31][32][33] which is supported by our between-group analysis.CCK is a neurotransmitter causing satiety after a meal by affecting the central nervous system, and hence it has close relationship with ghrelin. It can be said that ghrelin starts the meal while CCK ends it.…”
supporting
confidence: 77%
“…In this respect, although the distribution of our data is non-parametric, we can state that preacupuncture levels of insulin were in the higher centiles and postacupuncture values decreased to the lower centiles. This suggests normalisation of insulin values and improved insulin sensitivity with acupuncture treatment, [31][32][33] which is supported by our between-group analysis.CCK is a neurotransmitter causing satiety after a meal by affecting the central nervous system, and hence it has close relationship with ghrelin. It can be said that ghrelin starts the meal while CCK ends it.…”
supporting
confidence: 77%
“…Other studies indicated that acupuncture improved both hyperglycemia and insulin resistance (11,15). In animals, electroacupuncture (EA) has been shown to improve insulin resistance or sensitivity (10,25,26,31,37) and reduce plasma FFA (32). In the current study, we hypothesized that EA reduces elevated blood glucose level in a mouse model of insulin resistance, and the mechanism may be via the suppression of FFA.…”
mentioning
confidence: 99%
“…Acupuncture is also a safe intervention in the hands of competent practitioners. Yamashita et al [17] prospectively evaluated 55,291 acupuncture treatments administered by acupuncturists with medical training and documented only 64 adverse events (0.12%) [18]. All of those adverse events were minor, with the most common being bruising, dizziness, perspiration, discomfort, and dermatitis; warm needle acupuncture is safe and may be effective as an adjunct in reducing the number of RA patients.…”
Section: Discussionmentioning
confidence: 99%